Primary Brainstem Hemorrhage: A Review of Prognostic Factors and Surgical Management - Chen, Danyang; Tang, Yingxin; Nie, Hao; Zhang, Ping; Wang, Wenzhi; Dong, Qiang; Wu, Guofeng; Xue, Mengzhou; Tang, Yuping; Liu, Wenjie; Pan, Chao; Tang, Zhouping (Frontiers in Neurology, 2021)
Primary brainstem hemorrhage (PBSH) is related to a poor prognosis and high mortality. Three prognostic factors were identified for PBSH, including clinical factors, neuroradiological factors and neurophysiological factors. The development and presentation of scoring systems for PBSH are also presented in this review. There is a lack of high-quality clinical trials for the surgical treatment of PBSH, and the surgical timing and indicators remain unclear. Furthermore, the four most common surgical procedures are discussed, and their advantages and disadvantages are compared. The ongoing STIPE trial should provide additional evidence for the surgical treatment of PBSH.